Sistem Pendukung Keputusan Penentuan Aplikasi Jasa Pemesanan Makanan Online Terbaik Dalam Menerapkan Metode OCRA - Mohammad Aldinugroho Abdullah; Gandung Triyono; Rima Tamara Aldisa (Universitas Budi Darma, 2023)
In using online food ordering service applications, the existence of a Decision Support System (DSS) with the OCRA method is very helpful in choosing the best alternative. The application of a Decision Support System with the OCRA method gives important value to the predetermined criteria, so that the best alternative can be selected objectively and measurably. In choosing the best online food ordering service application. the use of DSS can increase the effectiveness and efficiency in decision making, thus bringing a positive impact on the development of the business. So from the results obtained from research regarding determining the best online food ordering service application is alternative A5 (GoFood) with a value of 0.2000.